2021
DOI: 10.1016/j.chemosphere.2020.128610
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of chemicals of environmental concern in crumb rubber and water leachates from several types of synthetic turf football pitches

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 19 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…In addition, the addition of rubber from used tyres is widely used in many types of binders such as gypsum, epoxy resins, Energies 2024, 17, 14 6 of 39 bitumen, and plastic composites [53][54][55]. Finely ground rubber is also used as an infill for football fields with artificial turf and as one of the main ingredients in the production of basketball substrates, as well as athletic treadmills [56,57]. However, the polycyclic aromatic hydrocarbons, volatile organic hydrocarbons, heavy metals, plasticizers, and other additives present in the rubber particles that enhance the strength of the rubber can be leached by rainwater from the rubber structure and enter the groundwater, resulting in health risks [56].…”
Section: Materials Recoverymentioning
confidence: 99%
“…In addition, the addition of rubber from used tyres is widely used in many types of binders such as gypsum, epoxy resins, Energies 2024, 17, 14 6 of 39 bitumen, and plastic composites [53][54][55]. Finely ground rubber is also used as an infill for football fields with artificial turf and as one of the main ingredients in the production of basketball substrates, as well as athletic treadmills [56,57]. However, the polycyclic aromatic hydrocarbons, volatile organic hydrocarbons, heavy metals, plasticizers, and other additives present in the rubber particles that enhance the strength of the rubber can be leached by rainwater from the rubber structure and enter the groundwater, resulting in health risks [56].…”
Section: Materials Recoverymentioning
confidence: 99%
“…The released substances that previous studies have identified from consumer products made of TCR granules include polycyclic aromatic hydrocarbons 6 13 , phthalates 10 , 12 , 13 , vulcanization additives 11 , 13 , and metal elements such as Al, As, Ba, Ca, Co, Cr, Cu, Cd, Fe, K, Li, Mg, Mo, Ni, Pb, Se, Sr, Tl, V, and Zn 7 12 , 14 – 18 . The organic contaminants probably resulted from the decomposition of rubber polymers and vulcanization accelerators, plasticizers during tire shredding and grinding; the metals primarily originated from nature rubber itself, the metal oxides catalysts for vulcanization and residuals of steel belt wires for the tire shreds and chips 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Twenty four metals were identified in 13 artificial-turf playfields; among these, Zn (1–19 g/kg) exceeded substantially the pertinent standards, by up to two orders of magnitude 9 . Furthermore, weak acid or outdoor solutions such as seawater have been applied to simulate the effect of real-life weathering on the slow leaching of metals 13 , 19 , 26 . An Italian study found that the most abundant metals were Zn, Fe, and Co in seawater leachate 19 .…”
Section: Introductionmentioning
confidence: 99%
“…This material, formed by end-of-life tires contains high concentrations of PAHs, heavy metals, plasticizers, and hazardous organic compounds [18][19][20][21]. Some studies have demonstrated the transfer of toxic compounds from the crumb rubber to the runoff water and air [22,23], although most of them are simulated studies at laboratory scale [24,25]. Only few studies include real air samples from recycled rubber facilities, being most of them focused on PAHs analysis by active [26,27] or passive [28] sampling.…”
Section: Introductionmentioning
confidence: 99%